Decreased RORC expression and downstream signaling in HTLV‐1‐associated adult T‐cell lymphoma/leukemia uncovers an antiproliferative IL17 link: A potential target for immunotherapy?. Issue 7 (18th December 2018) - Subramanian, Kritika; Dierckx, Tim; Khouri, Ricardo; Menezes, Soraya Maria; Kagdi, Huseini; Taylor, Graham P.; Farre, Lourdes; Bittencourt, Achilea; Kataoka, Keisuke; Ogawa, Seishi; Van Weyenbergh, Johan
Abstract : Retinoic acid‐related drugs have shown promising pre‐clinical activity in Adult T‐cell Leukemia/Lymphoma, but RORC signaling has not been explored. Therefore, we investigated transcriptome‐wide interactions of the RORC pathway in HTLV‐1 and ATL, using our own and publicly available gene expression data for ATL and other leukemias. Gene expression data from ATL patients were analyzed using WGCNA to determine gene modules and their correlation to clinical and molecular data. Both PBMCs and CD4 + T‐Cells exhibited decreased RORC expression in four different ATL cohorts. A small subset of RORC hi ATL patients was identified with significantly lower pathognomonic CADM1 and HBZ levels but similar levels of other ATL markers (CD4/CD25/CCR4), hinting at a less aggressive ATL subtype. An age‐dependent decrease in RORC expression was found in HTLV‐1‐infected individuals, but not in healthy controls, suggesting an early molecular event predisposing to leukemogenesis. Genes upstream of RORC signaling were members of a proliferative gene module (containing proliferation markers PCNA/Ki67), whereas downstream members clustered in an anti‐proliferative gene module. IL17C transcripts showed the strongest negative correlation to PCNA in both ATL cohorts, which was replicated in two large cohorts of T‐ and B‐cell acute lymphoid leukemia (ALL). Finally, IL17C expression in purified CD4 + CCR4 + CD26‐CD7‐ "ATL‐like" cells from HTLV‐1‐infected individuals and ATL patients was negatively correlated with clonality, underscoring a possible antileukemic/antiproliferative role. In conclusion, decreased RORC expression and downstream signaling might represent an early event in ATL pathogenesis. An antiproliferative IL17C/PCNA link is shared between ATL, T‐ALL and B‐ALL, suggesting (immuno)therapeutic benefit of boosting RORC/IL17 signaling. Abstract : What's new? Drugs that affect the retinoic acid pathway are of interest for the treatment of adult T‐cell leukemia (ATL). Here, investigation of the role of retinoic acid‐related orphan receptor C (RORC), a regulator of the proinflammatory Th17/IL‐17 axis, reveals a prevailing occurrence of low RORC expression among ATL patients. By comparison, fewer patients exhibited a RORC hi phenotype, which was associated with reduced levels of pathognomonic biomarkers CADM1 and HbZ, indicating a protective role for elevated RORC. An antiproliferative link was identified between RORC and IL17C. The data suggest that strategies to increase RORC/IL17C signaling could be important to improving ATL outcomes.